2017
DOI: 10.1039/c6cp06634h
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of oxidation states of platinum nanoparticles on a polymer electrolyte fuel cell electrode by near ambient pressure hard X-ray photoelectron spectroscopy

Abstract: We performed in situ hard X-ray photoelectron spectroscopy (HAXPES) measurements of the electronic states of platinum nanoparticles on the cathode electrocatalyst of a polymer electrolyte fuel cell (PEFC) using a near ambient pressure (NAP) HAXPES instrument having an 8 keV excitation source. We successfully observed in situ NAP-HAXPES spectra of the Pt/C cathode catalysts of PEFCs under working conditions involving water, not only for the Pt 3d states with large photoionization cross-sections in the hard X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 53 publications
3
50
1
Order By: Relevance
“…Despite recent advances, nearly all in situ studies of energyrelated materials have been performed using bulk sensitive spectroscopies, such as hard X-ray XAS and XRD. The recent coupling of operational systems with surface sensitive techniques, such as X-ray photoelectron spectroscopy (XPS), provides significant opportunity for shedding new light on phenomena occurring at the solid/liquid electrified interface (38,39,40,41,42,43,44,45,46,47,48). In this work, we study, under operando conditions, the chemical and structural evolution of different conformal CoO x catalyst layers formed by plasma-enhanced atomic layer deposition (PE-ALD) on p + -Si substrates (37) as a function of the applied electrochemical potential.…”
mentioning
confidence: 99%
“…Despite recent advances, nearly all in situ studies of energyrelated materials have been performed using bulk sensitive spectroscopies, such as hard X-ray XAS and XRD. The recent coupling of operational systems with surface sensitive techniques, such as X-ray photoelectron spectroscopy (XPS), provides significant opportunity for shedding new light on phenomena occurring at the solid/liquid electrified interface (38,39,40,41,42,43,44,45,46,47,48). In this work, we study, under operando conditions, the chemical and structural evolution of different conformal CoO x catalyst layers formed by plasma-enhanced atomic layer deposition (PE-ALD) on p + -Si substrates (37) as a function of the applied electrochemical potential.…”
mentioning
confidence: 99%
“…[372,373] BL36XU has also been a trailblazer in combining ambient pressure environments with operando setups for fuel cells, which will be discussed in detail in Section 3.3.3. [372,374,375] Today, a number of AP-HAXPES beamlines is operational, including P22 (PETRA III), X07MB (SLS), and 9.3.1 (ALS). [57,58,376] In addition, beamline 8A at the Pohang Accelerator Laboratory, which is set up as a soft X-ray AP-HAXPES endstation, uses an off-line Cr Kα source to perform AP-HAXPES.…”
Section: Ambient Pressure Haxpes (Ap-haxpes)mentioning
confidence: 99%
“…The interaction between gas molecules and polymeric materials is also possible: for example, the interaction of water to hydrophilic polymer chains in superabsorbent hydrogel such as a soft contact lens can be probed effectively [146]. In the nanocomposite systems, a lower number of studies using NAP-XPS can be found in the literature regarding the interaction of relevant molecules with inorganic fillers on or near the surface of the nanocomposite, e.g., the chemical state of Pt in Pt/C electrodes under humid condition [148]. Probing the interaction at organic/inorganic interfaces was recently attempted: Pletincx et al investigated the mechanism of the interactions among three components of water vapor, poly(methyl methacrylate) (PMMA) chain, and aluminum oxide surface [149].…”
Section: New Opportunity With Emerging X-ray Based Techniques Enablinmentioning
confidence: 99%